The synthesis and structure of C4 symmetric resorcinarenes - McIldowie, Matthew (Curtin University, 2007)
This study investigates methods for the synthesis and resolution of chiral resorcinarenes.The first direct synthesis of C4 dissymmetric resorcinarenes by the Lewis acid catalysed condensation of 3-alkoxyphenols and alkyl aldehydes was developed. The chirality of these novel resorcinarenes was demonstrated by nuclear magnetic resonance spectroscopy (n.m.r.) and enantioselective HPLC. The structure and physical properties of the new materials were characterised by several methods including X-ray crystallography.Resolution of the chiral resorcinarenes was achieved on a multi-gram scale by either formation of their diastereomeric camphorsulfonate esters or diastereomeric "amide" derivatives followed by flash chromatographic separation. The absolute configuration of one resorcinarene camphorsulfonate diastereomer was determined by X-ray crystallography and the stereochemistry of the related diastereomers assigned based on spectroscopic and chromatographic properties. Hydrolysis of the resolved resorcinarene camphorsulfonate diastereomers afforded the C4 symmetric resorcinarenes of known absolute stereochemistry. The absolute configuration of one resorcinarene "amide" diastereomer was also determined by X-ray crystallography.Functionalisation of the resorcinarene racemates with 2- and 3-picolyl ethers afforded a number of resorcinarene based pyridine ligands. The complexation behaviour of the ligands was examined and X-ray crystallographic data obtained for complexes with silver(I) and copper(II) salts.A significant proportion of the work described in this thesis has been published in four separate peer reviewed papers which have been attached as appendices 12-15.